Kepastian Hukum Sertipikat Hak Atas Tanah di Atas Laut - Nita Anggraini; Rudy Iskandar Ichlas; Multi Sri Asnani (SENTRI: Jurnal Riset Ilmiah, 2025)
This study examines the regulatory challenges arising from the utilization of marine space for the construction of permanent buildings and their implications for the exercise of state authority in Indonesia. The problem emerges from a normative dualism between agrarian law and maritime law. The Basic Agrarian Law confines the regime of land rights and state control to terrestrial areas, while maritime regulations merely regulate the administrative licensing of marine space utilization without recognizing permanent legal rights. This regulatory gap creates legal uncertainty and constrains government institutions from acting consistently with the principle of legality, particularly in determining the legal status of permanent structures built over water, such as the Al-Alam Mosque in Kendari. The research aims to analyze the impact of this normative vacuum on governmental authority in providing legal certainty and to assess the juridical consequences resulting from the absence of a clear legal basis governing permanent buildings in marine areas. A normative juridical method is employed, using statutory analysis and conceptual approaches to examine regulatory hierarchy, coherence between legal regimes, and the scope of administrative authority in managing marine space. The findings reveal that the absence of explicit norms regulating the legal status of marine space for permanent structures prevents government bodies from issuing legally sustainable decisions that ensure long-term protection. The study contributes to legal discourse by clarifying structural weaknesses within the existing regulatory framework and provides practical insights for policymakers by emphasizing the urgency of establishing integrated legal instruments to ensure legal certainty, and institutional coherence.